2006
DOI: 10.1002/mawe.200600022
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium‐substituted hydroxyapatite ceramics

Abstract: The effect of the addition of magnesium (up to 10 wt%, expressed as MgO) on the phase composition, the microstructure and the mechanical properties of hydroxyapatite-based ceramics (HA) was studied by X-ray powder diffraction, infrared spectroscopy, scanning electron microscopy, and mechanical testing. Doping with magnesium did not change the crystal lattice of HA but, due to an isomorphous substitution of Mg 2+ for Ca 2+ , it caused a decrease in the average grain size, an increase of microporosity, a removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…It can be observed that in the case of 0.25Mg-HAp and 0.5Mg-HAp nanopowders, the particle size decreased with Mg content, in good agreement with Zyman et al 29 As reported in Table 2, both as-dried samples showed a (Ca + Mg)/P ratio close to the stoichiometric value of HAp (i.e. 1.667) and presented a low volume fraction of ␤-TCP (Table 3a).…”
Section: Specific Surface Area Of Pure and Mg-substituted Hydroxyapatsupporting
confidence: 91%
See 1 more Smart Citation
“…It can be observed that in the case of 0.25Mg-HAp and 0.5Mg-HAp nanopowders, the particle size decreased with Mg content, in good agreement with Zyman et al 29 As reported in Table 2, both as-dried samples showed a (Ca + Mg)/P ratio close to the stoichiometric value of HAp (i.e. 1.667) and presented a low volume fraction of ␤-TCP (Table 3a).…”
Section: Specific Surface Area Of Pure and Mg-substituted Hydroxyapatsupporting
confidence: 91%
“…Moreover, as the Mg content increased, a slight shift of the OH − peak at 3572 cm −1 and a considerable broadening of the 700-1700 cm −1 phosphate bands were observed. 29 In detail, in the case of 1.0Mg-HAp sample, extra peaks at 942, 948, 962, 972, 986 1 , 1044, 1090, 1120 cm −1 were detected. These bands can be ascribed to the PO 4 3− vibration modes characteristic of tricalcium phosphate, in good agreement with Pena and Vallet-Regi 30 (Fig.…”
Section: Samplementioning
confidence: 95%
“…Concerning the mechanical properties, Mg incorporation significantly decrements compressive strength and microhardness up to a Mg content of 1.8 wt% [67] and causes an increment of the fracture toughness with Mg amount up to 0.6 wt%, content very close to the magnesium concentration in the natural bone mineral component. These experimental evidences were ascribed to the decremented average grain size, the increased microporosity, and the formation of a weak intergranular boundary [61,67].…”
Section: Influence Of Mgmentioning
confidence: 97%
“…These experimental evidences were ascribed to the decremented average grain size, the increased microporosity, and the formation of a weak intergranular boundary [61,67].…”
Section: Influence Of Mgmentioning
confidence: 99%
See 1 more Smart Citation